“Regular Television Put to Shame by Negro Production”: Picturing a Black World on Black Journal - Heitner, Devorah (Watching While Black, 2012)
In the first episode of Black Journal , before the opening credits, comedian Godfrey Cambridge appears dressed in overalls and a painter’s cap with a paint roller in hand and methodically paints the television frame. To the viewer, it appears that his or her television is being painted black from the inside—a potent visual symbol from the first national Black public affairs program. Initially, though, the symbol emphasizes a visual challenge to the absence of Black faces on television—a show that “looks” Black, because of the visibility of its Black hosts and reporters, but where whites still have significant
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Identity and Performance in Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography - Heitner, Devorah (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In novel ways, and from a surprising location, Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography (1995) explores some of the same dilemmas that earlier African American expatriate artists promulgated, using their time abroad as a win dow onto America, while relishing the nurturing possibilities of partial escape from American racism. Some of the most complex and insightful observations about America and American racism have been crafted by African American expatriate artists such as James Baldwin and Josephine Baker. These artists’ depictions of their encounters abroad complicate our understandings of American identity and American racism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé